2021
DOI: 10.1037/int0000253
|View full text |Cite
|
Sign up to set email alerts
|

Animal-assisted psychotherapy for developmental trauma through the lens of interpersonal neurobiology of trauma: Creating connection with self and others.

Abstract: Chronic maltreatment in childhood has been found to have serious deleterious effects on the child’s present and future medical and psychological health, self-regulation, and ability to function in interpersonal relationships, resulting in developmental trauma (DT). In recent years, researchers in the field of neurobiology have discovered pervasive neurological implications of maltreatment, negatively affecting the functioning of the neurological system, bringing further understanding of the emotional and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 118 publications
1
13
0
Order By: Relevance
“…Previous research already showed that some patients with acquired brain injury profit more from the animal’s presence than others 36 . Animal-assisted psychotherapy is thought to be especially helpful for patients experiencing difficulties in interpersonal relationships 64 , 65 and survivors of developmental trauma 48 . Further studies should focus on process- and relationship-based measures to better understand effects of animal-assistance on the therapeutic alliance.…”
Section: Limitations Strengths and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research already showed that some patients with acquired brain injury profit more from the animal’s presence than others 36 . Animal-assisted psychotherapy is thought to be especially helpful for patients experiencing difficulties in interpersonal relationships 64 , 65 and survivors of developmental trauma 48 . Further studies should focus on process- and relationship-based measures to better understand effects of animal-assistance on the therapeutic alliance.…”
Section: Limitations Strengths and Future Directionsmentioning
confidence: 99%
“…Integrating a domesticated animal in a psychotherapeutic intervention, delivered by a psychotherapist with additional certification in animal-assisted therapy, is conceptualized as animal-assisted psychotherapy 46 , 47 . Conducted in a highly relational environment, animal-assisted psychotherapy is discussed to be an approach that lowers barriers to utilization of psychotherapeutic interventions 48 by enriching the therapeutic setting through a context of normality and non-evaluation which helps patients to feel secure and accepted 49 , 50 . Animals are hypothesized to act as social-support figures 51 .…”
Section: Introductionmentioning
confidence: 99%
“…However, an established and distorted Model of Self and Others (MoS and MoO) in patients with attachment-related problems such as CPTSS, DESNOS, or DTD makes it difficult to establish long-term, productive, intersubjective relationships—in effect, to engage in the therapeutic healing process [ 16 , 20 , 35 ]. Many patients in this population jump from one therapy to another, reflecting a sense that the treatments are not in line with their needs [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients in this population jump from one therapy to another, reflecting a sense that the treatments are not in line with their needs [ 36 , 37 , 38 , 39 ]. Amongst others, the field of Animal-Assisted Psychotherapy (AAP) seeks ways of facilitating the psychotherapy process by the inclusion of animals in the therapeutic process [ 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation